The Role of Patient Education in Low Anterior Resection Syndrome: A Systematic Review - P. Tang; R. Tovel; H. Ong; David Proud; Adele Burgess; Eleanor Watson; Wui Yeat Chen; David Lam; Helen Mohan (Journal of Cancer Education, 2025)
Low anterior resection syndrome (LARS) is a significant complication after sphincter-preserving rectal cancer surgery and negatively impacts a patient’s quality of life. Treatment of LARS is multimodal, and many treatments require engagement from the patient. Understanding the complex array of treatment options and the potential additive effects of different therapies can be difficult. This systematic review aims to assess the role of patient education in treatment of LARS in colorectal cancer patients. A systematic literature search was conducted on PubMed, EMBASE and Ovid Medline according to the PRISMA guidelines for articles published from 1946 to October 2023 and registered with PROSPERO: 42,023,434,601. Studies that reported on clinical outcomes of patients with LARS that underwent any educational intervention were included for this review. Results from five publications including 368 patients with LARS were reviewed for analysis. Three interventions were delivered to symptomatic patients postoperatively and two to all patients who underwent low anterior resection preoperatively. Five trial protocols were also included for analysis, including three preoperative and two postoperative interventions Education interventions were often delivered alongside co-interventions such as medications and pelvic floor physiotherapy. Four studies reported improvement of mean LARS scores and quality of life measures related to the education intervention and associated co-interventions. Patient education has a positive impact towards improving functional outcomes in patients with LARS following resection for rectal cancer. In practice, it is often used in conjunction with other interventions. Determining optimal content and delivery methods is a target for future research.